Philippines Basic Education : Public Expenditure Review - World Bank (World Bank, Washington, DC, 2020)
Countries invest in basic education to provide their citizens with the means to acquire the foundations for building human capital. Countries with good school education systems provide equity of access, i.e., encourage all children, irrespective of gender, household income, and geographical location, from the early years onwards, to participate in the full cycle of education. Good education systems have learning environments that lead to strong learning outcomes. Since education is the basis for human capital development and improves individual productivity and earnings, good education systems contribute both to economic growth and social equity. This report looks at the role played by public expenditure in improving access, equity, quality, and learning in basic education in the Philippines. It builds on work undertaken earlier, especially the Basic Education Public Expenditure Review and the Philippines Public Education Expenditure Tracking and Quantitative Service Delivery Survey. Specifically, this review provides a comparative picture of sector performance, where possible, between the periods 2002 to 2008 and 2009 to 2017, the former being the period studied by BEPER (2012). Chapter one looks at quantity and quality in basic education, Chapter two examines equity issues, and chapter three looks at patterns of public expenditure in basic education. In the remaining section of this introduction, a brief description of how basic education is managed and financed in the Philippines is provided.